A miséria da piedade: o governo da pobreza no dispositivo da caridade (Fortaleza, 1880-1930) - Ferreira, Antônio Nelorracion Gonçalves (2019)
Understand charity as a device, one tries to analyze its political, economic and social strategies in the government of the urban poverty of Fortaleza. From the conception of the donor practices as cultural artifacts – going beyond a classic analysis on the practices of solidarity that are restricted to the limits of the assistance policies, of markedly economicist character – it is tried to show its forms of expression through the language, the rituals, symbols, emotions and Power. The effects of a politics based on piety / charity, its relations with disciplinarization, domestication, government of the other, and mechanisms of social exclusion and segregation are other relevant aspects analyzed in the research. It is also investigated to what extent this charitable government enabled certain conditions for exercise of capitalist discipline. In addition, it seeks to understand the role of charity in Fortaleza’s assistance actions and its contribution to the recatholization of society.